An instrumental analysis of vowels in Malacca Portuguese Creole / Chan Min En - Chan, Min En (2014)
This paper examines the vowel system of present day Malacca Portuguese Creole (MPC) which is in danger of extinction. The research questions that the study addresses are: (1) What are the characteristics of monophthong vowels in MPC based on their acoustic properties?; (2) To what extent are the MPC monophthong vowels found in this study similar to those described in the literature?; (3) How do the MPC monophthong vowels compare to similar vowels in Malay, Malaysian English and European Portuguese? Conversational data were collected from five female speakers, henceforth known as language consultants (LC), who are native speakers of MPC, and who have spent the majority of their lives in the Portuguese Settlement in Malacca. Vowels were extracted from the recordings as long as they did not have neighbouring nasals and approximants which may have affected the quality of targeted vowels. A total of 1083 monophthongs were extracted for analysis. The first (F1) and second formants (F2) and the duration of the vowels were measured using Praat version 5.2.04. Measurements were carried out using linear-prediction-based formant tracks overlaid on spectrograms of the targeted vowels. F1 and F2 values were measured at the mid-point of the vowels. The results suggest that there are six MPC monophthongs compared to the eight proposed previously, with a notable absence of /o/ and /ɛ/. Considerable variation was found within and between LCs in the way each of the vowels was produced. There were also noticeable overlaps between /i/ and /e/ suggesting that they were being used interchangeably by the LCs. The quality of some of the vowels found in this study was also found to be different from those previously described. In relation to Malay, Malaysian English and European Portuguese, MPC vowels were generally found to be closer to Malay in terms of vowel quality and inventory. The reduced vowel inventory of MPC compared to European Portuguese, albeit the current day variety, reflects its status as a Creole. Based on the reduced vowel inventory, the variation in the way that vowels are produced, the overlaps between vowels and the possible influence from other local languages, the findings point towards the possible phonological instability of this endangered language. Further, they mirror the changes found in terms of vocabulary loss and substitution in MPC found by other researchers. Keywords: Malacca Portuguese Creole, Kristang, phonetics, instrumental analysis, vowels, monophthongs.